General Management Considerations for Placenta Accreta Spectrum - Einerson, Brett D.; Sandlin, Adam T.; Afshar, Yalda; Sharawi, Nadir; Fox, Karin A.; Newton, J. M.; Shainker, Scott A.; Pezeshkmehr, Amir; Carusi, Daniela A.; Moroz, Leslie (American Journal of Perinatology, 2023)
The ideal management of a patient with placenta accreta spectrum (PAS) includes close antepartum management culminating in a planned and coordinated delivery by an experienced multidisciplinary PAS team. Coordinated team management has been shown to optimize outcomes for mother and infant. This section provides a consensus overview from the Pan-American Society for the Placenta Accreta Spectrum regarding general management of PAS.
Keywords: multidisciplinary care; hysterectomy; postpartum; cesarean; endovascular intervention